1988
DOI: 10.3171/jns.1988.69.4.0613
|View full text |Cite
|
Sign up to set email alerts
|

Epidural hibernoma as a complication of corticosteroid treatment

Abstract: Centripetal fat deposition is a well-recognized consequence of excessive use of corticosteroids, either endogenous or exogenous. Recently, several patients receiving large doses of corticosteroids have suffered compressive myelopathies due to excessive epidural fat collections, labeled "epidural lipomatosis." Two of these have been children, and a third child is reported here. This child was receiving chronic steroids for juvenile rheumatoid arthritis when he presented with such a myelopathy, which was confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Although the mean age of patients with SL reported in literature is 43 years, the disorder tends to occur at a younger age in male patients 2 3. The youngest patient with SL was a 6-year-old boy who was receiving high-dose steroid therapy 4. Our case report describes an overweight patient discovered to have a SEL in the thoracic spine.…”
Section: Discussionmentioning
confidence: 90%
“…Although the mean age of patients with SL reported in literature is 43 years, the disorder tends to occur at a younger age in male patients 2 3. The youngest patient with SL was a 6-year-old boy who was receiving high-dose steroid therapy 4. Our case report describes an overweight patient discovered to have a SEL in the thoracic spine.…”
Section: Discussionmentioning
confidence: 90%
“…In the 17 surgical patients with available data, the time course of patients' neurological deterioration was noted in days [6][7][8]10,11,13,14,17,18,20,23,24,[26][27][28][29][30][32][33][34]36,37]. The duration of symptoms refers to the period of time between when the patient first reported noticing symptoms and their definitive surgery.…”
Section: Acuity Of Symptom Onsetmentioning
confidence: 98%
“…In 22 patients, both the cumulative dose of prednisone and the extent of ultimate recovery could be assessed [7,8,10,11,13,14,17,18,20,[22][23][24][26][27][28][29][30]. Five of these patients were managed conservatively with reduction of their steroid dose, 13 were managed with surgery alone and four were managed with both surgery and steroid reduction.…”
Section: Cumulative Steroid Dosementioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies showed mild elevation of alanine-aminotransferase 53-77 U/1 (1 040), elevated triglyceride 4.2 mmolil (0.4-1 .S), low serum testosterone 6.1 nmol/l (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), and the serum cortisol was normal.…”
mentioning
confidence: 99%